Preventing traffic accidents at traffic junction with obstructed view using V2X communication - Yeo, Pei Chi (2018)
The automotive industry is fast changing. Newer models of cars come with a myriad of smart functions such as self-parking, blind spot warning and of course, self-driving capabilities. However, these are merely supported by a variety of sensors making it more of a sensory experience. For vehicles to be truly intelligent, they would need to communicate with one another.